STRATEGI PENGELOLAAN KAWASAN HUTAN MANGROVE SEBAGAI KAWASAN HUTAN PRODUKSI DI KABUPATEN MAROS SULAWESI SELATAN, INDONESIA - Amal Arfan; Rosmini Maru; Syafruddin Side; Alief Saputro (Jurnal Environmental Science, 2021)
Sustainable production forest is a forest that can produce products of economic value that can be used for the needs of life today and in the future. The benefits of various products and services from mangrove forests have been felt by humans, both in the form of wood and non-wood products. The population of this research is people age 20 - 60 years who live around the mangrove forest area of the coast of Maros Regency. The sampling technique is carried out using proportional stratified random sampling, which is based on the stratification of the types of activities around the mangrove forest area. Data collection techniques used are adjusted to the required data including, Direct Observation, Documentation, In-depth Interview with the Participatory Rural Appraisal approach, Focus Group Discussion, to determine the distribution and extent mangrove forest area in South Sulawesi. After that, the internal and external factors that are supporting and inhibiting use the SWOT analysis.  The results showed that the strategy of managing mangrove forest areas as production forest areas in Maros Regency is develop the potential of sustainable and economically valuable mangrove forest resources through eco-friendly cultivation and capture businesses, increasing the role of ngos to increase community knowledge and awareness in mangrove management, providing counseling and training on crab processing., community empowerment through fishermen / farmer groups to create a household scale industry based on mangrove resources, training and mentoring of farmer/fisherman/women's groups in utilizing mangrove forest resources